Embedded Liberalism and Health Populism in the UK in a Post-Truth Era - Dalingwater, Louise (2023)
The National Health Service (NHS), as a symbol of public health protection in the UK, was weaponised in pro-Brexit debates. It was suggested that European integration might inherently have undermined embedded liberalism and notably contributed to what Ruggie described as the “unbundling of sovereignty” (Ruggie, 1993). The manipulation of the NHS by right-wing populists has already been the focus of a number of articles, but calls to protect public health care from global threats have also come from left-wing politicians and activists. This article is particularly interested in socialist populist appeals to protect health care. It aims to show that for socialists the compromise between capital and labour and the protection of welfare systems, which is referred to as embedded liberalism, has not been achieved. In fact, furthering trade and investment is currently seen to be compromising the last remnants of a welfare state, which is embodied by the NHS in the UK. This conceptual article will thus start by presenting the theory of embedded liberalism. It will then establish the link between the breakdown of embedded liberalism in relation to health care systems. It will finally present populist and activist narratives on health and the UK’s national health service from an international perspective. It draws on secondary literature and a corpus of popular press articles and grey literature produced by civil society organisations.